Implementation Of Regional Regulation 19 Of 2022 Concerning The Authority Of The Civil Service Police Unit in Controlling Street Vendors in Situbondo Regency - Moh. Ali Imron; Priyanto Priyanto; Dian Ferriswara; Sri Kamariyah (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to describe and analyze: The Implementation of Regional Regulation 19 of 2022 concerning the Authority of the Civil Service Police Unit in the Control of Street Vendors in Situbondo Regency. 2. The obstacles faced and what solutions have been carried out by the Civil Police in Controlling Street Vendors in Situbondo Regency. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Pamong Praja Police Unit in controlling Street Vendors in Situbondo Regency Based on article 19 of 2022 article 2 has been running in accordance with its duties and functions. In regulating street vendors, four policy implementation models are Communication Factors, Disposition Resources or Attitudes and Bureaucratic Structures. The obstacles faced include human resource factors, both in terms of communication skills and approaches, as well as the number of members. The solutions carried out include Improving the Quality and Quantity of Human Resources at Satpol PP. By conducting an intensive coaching program to improve the competence and expertise of Satpol PP members in collaborating with the community to create community security and increase the number of Satpol PP members who are tasked with controlling street vendors. Improve socialization programs to the community and improve themselves by taking a persuasive approach and acting elegantly by not prioritizing arrogance as a security apparatus.